PROFIL PROTEIN DAN ASAM AMINO KEONG IPONG-IPONG (Fasciolaria salmo) PADA PENGOLAHAN YANG BERBEDA - Sri Purwaningsih; Ella Salamah; Gian P Apriyana (Jurnal Gizi dan Pangan, 2013)
Ipong-Ipong (Fasciolaria salmo) snail is a mollusk from marine gastropod class in Cirebon, West Java which is consumed by public and believed to improve health, but no research on the protein and amino acid content. This study aimed to determine the proximate content, acid insoluble ash, amino acids (before and after treatment), and content of taurine on the best methods. The research was conducted in two parts. The first part covers sampling, identification, preparation, determination of size and weight, calculation of body recovery, processing, and organoleptic tests. The second part consists of processing treatments boiling (100ºC for 15 minutes), steaming (100ºC for 20 minutes), and boiling with the addition of 3% salt for 15 minutes. The results showed that the treatment gives a significant effect in fat, protein, water, ash and acid insoluble ash content (α=0.05). The highest content of essential amino acids in Ipong-ipong snail was arginine and non-essential amino acid was glutamic. The treatment method causes decreased in amino acid content. Steaming resulted in a decrease of taurine content of 164.17 mg/100 g to 149.62 mg/100 g.